Why Company Should Adopt Integrated Reporting? - Hoque, Mohammad Enamul (International Journal of Economics and Financial Issues, 2017)
Sustainability and transparency issues have been evolving the nature of corporate reporting. On these issues stakeholders are very keen to get access financial and nonfinancial information on companies’ business activities and sustainable value creation. Despite availability of information, yet many stakeholders cannot use pertinently the disclosed information due to separation of reports. Thus, ‘Integrated Report’ brings together financial and nonfinancial measure in one-piece of the report. It also shows the links among financial and nonfinancial performance metrics. This paper highlights integrated reporting as the holistic reporting approach for company and discusses the potentiality of a single report. Specifically, what integrated report can do for companies and stakeholder, for instance, integrated report for sustainability and CSR reporting, improvement in stakeholder engagement process and integrated thinking lead to changes in corporate behaviour as well as for enchancing reputation and performance. Hence, the paper justifies reasons why companies should adopt integrated reporting as reporting tools. Keywords: Integrated reporting; integrated thinking; stakeholder engagement; sustainability reporting JEL Classifications: G3, G380, M480